2018
DOI: 10.1038/s41388-017-0054-6
|View full text |Cite
|
Sign up to set email alerts
|

AATF suppresses apoptosis, promotes proliferation and is critical for Kras-driven lung cancer

Abstract: A fundamental principle in malignant tranformation is the ability of cancer cells to escape the naturally occurring cell-intrinsic responses to DNA damage. Tumors progress despite the accumulation of DNA lesions. However, the underlying mechanisms of this tolerance to genotoxic stress are still poorly characterized. Here, we show that replication stress occurs in Kras-driven murine lung adenocarcinomas, as well as in proliferating murine embryonic and adult tissues. We identify the transcriptional regulator AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 64 publications
2
27
0
Order By: Relevance
“…AATF is known to promote cell proliferation and also survival by inducing cell cycle arrest, autophagy, DNA repair, and inhibition of apoptosis . Recent studies have shown that AATF is up‐regulated in breast and lung cancer and leukemia . The role of AATF in HCC in the setting of NAFLD and the associated molecular mechanisms were not known.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…AATF is known to promote cell proliferation and also survival by inducing cell cycle arrest, autophagy, DNA repair, and inhibition of apoptosis . Recent studies have shown that AATF is up‐regulated in breast and lung cancer and leukemia . The role of AATF in HCC in the setting of NAFLD and the associated molecular mechanisms were not known.…”
mentioning
confidence: 99%
“…(13)(14)(15)(16)(17) Recent studies have shown that AATF is up-regulated in breast and lung cancer and leukemia. (18)(19)(20) The role of AATF in HCC in the setting of NAFLD and the associated molecular mechanisms were not known.…”
mentioning
confidence: 99%
“…We generated mice lacking Aatf in tubular epithelial cells of the distal nephron (Aatf tko ) by crossing mice carrying a floxed Aatf allele 16 with the Ksp1.3/Cre line. 17 Aatf tko mice were born without any overt phenotype and in normal Mendelian ratios.…”
Section: Deletion Of Aatf In Distal Nephrons Leads To Kidney Dysfunctmentioning
confidence: 99%
“…Aatf floxed mice where exon 6 is flanked by loxP sequences (Aatf fl/fl mice 16 ) were mated with Ksp1.3/Cre mice 17 to generate a renal tubular epithelial cell-specific Aatf knockout mouse model (Aatf fl/fl ;Ksp1.3/Cre:pos, Aatf tko ). Cre-negative littermates (AATF fl/fl or AATF fl/wt ) were used as controls in this study.…”
Section: Conditional Knockout Mouse Modelsmentioning
confidence: 99%
“…As to human disease this protein has been implicated to play an important role in cancer biology, a hypothesis that is partly based upon its ability to inhibit apoptosis. AATF has previously been found to be amplified or overexpressed in both hematological and solid tissue tumors, to correlate with poor prognosis, relapse and reduced survival [4][5][6]9,10,46 and to mediate its effects on apoptosis by the modulation of p53 abundance and function 4,6 . Furthermore, increased ribosome biogenesis is not only employed by tumors to increase their proliferative potential but appears to be a risk factor for cancer onset on its own 47 .…”
Section: Discussionmentioning
confidence: 99%